Պատմական հուշարձանների վերականգնումը Մայրավանքում - Մերի Դանիելյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Армянская церковная архитектура оставила неизгладимый след во всемирном культурном наследии, добавив к уже существующим архитектурным стилям самобытный армянский стиль. The Armenian Church architecture had left an indelible imprint in the world cultural heritage adding Armenian and unique style to the range of architectural styles.
Keywords: History; Technology; Building construction; Museums; Collectors and collecting; Fine Arts; Sculpture